2022
DOI: 10.1111/njb.03580
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of medicinal plants of Pashat Valley, Bajaur, along Pakistan–Afghanistan border: a mountainous region of the Hindu Kush Range

Abstract: Medicinal plants are the primary and effective source to cure various human ailments throughout the globe. The remote area of the Pashat valley at the Pakistan-Afghanistan border is still unexplored to document ethnomedicinal knowledge and practices. In the current study, the contemporary investigation recorded the native acquaintance of remedial plants. A total of 73 plant species belonging to 68 genera and 46 families were used by traditional communities for the treatment of 40 different kinds of human disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…Additionally, it indicates use and effectiveness with few side effects (Hussain et al 2018). (Mlilo and Sibanda 2022;Bai et al 2022;Mohamed et al 2022;Haq et al 2022;Munir et al 2022) supported the present findings.…”
Section: Relative Frequency Of Citation (Rfc)supporting
confidence: 84%
“…Additionally, it indicates use and effectiveness with few side effects (Hussain et al 2018). (Mlilo and Sibanda 2022;Bai et al 2022;Mohamed et al 2022;Haq et al 2022;Munir et al 2022) supported the present findings.…”
Section: Relative Frequency Of Citation (Rfc)supporting
confidence: 84%
“…The comparative analysis of these 206 plants showed that similarity index ranges from 15.86% to 6.45% and the dissimilarity index ranged from 63.00% to 41.46%. The maximum level of the Jaccard index (JI) was found in the literature with the studies of Hussain et al (2022), Haq et al (2022, Ullah et al (2021), Hussain et al (2018b) and Aziz et al (2016) with JI values (24.8, 23.45, 22.8, 21.63 and 19.5% respectively (Table 5). The highest degree of similarity index with Aziz et al (2016) in the area of South Waziristan agency, Pakistan, revealed similarity in ethnic groups, geography and vegetation in both regions.…”
Section: Jaccard Index (Ji)mentioning
confidence: 74%
“…The relative frequency is calculated by dividing the frequency citation by the number of informants without considering the use of groups. In the ethnoveterinary study RFC stands for the ratio of informants who revealed the use plants of FC to the total number of informants for all plants surveyed (Kayani et al, 2014;Ibrar et al, 2015;Haq et al, 2022). RFC is defined by the following formula: RFC = CF/N RFC values range from 0 (when none of the informants cited the plants as useful) to 1 (when every informant reported the plants to be useful) (Mirzaman et al, 2023, Ibrar et al, 2015.…”
Section: Relative Frequency Citationmentioning
confidence: 99%